Infrastructure management and construction in urban areas with a different approach from traditional GIS design - Turk, Tarik; Gumusay, Mustafa Umit (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2008)
Infrastructure services, such as wastewater, water, natural gas, electricity and telecommunication services are the major application areas of UIS (Urban Information System). In Turkey, since the population in urban areas has been increasing rapidly and uncontrollably, infrastructure services have been extremely insufficient. After the destructive earthquake which happened in the Marmara region on 17(th) August 1999, the infrastructure system was seriously damaged. Use of GIS (Geographical Information System) has been an indispensable tool to control the infrastructure services more efficiently in case of such emergencies. The study area, to solve the problems of these services, was selected in the Sakarya province of the Marmara region. Since it is very difficult to control and manage these services damaged by the earthquake via conventional methods, an IIS (Infrastructure Information System) was designed and implemented. During the conceptual and logical design of the IIS, UML (Unified Modeling Language) was used which is the most important difference between traditional GIS and the IIS design. The created system has been tested with selected data to provide more economic, faster and more efficient infrastructure services in the province. Consequently, the IIS has been used to implement many processes, such as various spatial and non-spatial queries, and has been used in the solving of available infrastructure problems due to rapid population increase in the settlement areas, controlling and planning of the existing infrastructure systems, and contributing to e-Municipality for the infrastructure services. As UML diagrams were used in the conceptual and logical design of the IIS, geographical objects, non-geographical objects, as well as the relationships among them were shown visually. Hence, the IIS has been organized more easily.
Keywords: GIS; infrastructure management; spatial database design; UML; wastewater; water; Environmental Sciences & Ecology